2004
DOI: 10.1136/bmj.328.7430.26
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of support from volunteer counsellors for mothers considering breast feeding

Abstract: Objective To investigate whether offering volunteer support from counsellors in breast feeding would result in more women breast feeding. Design Randomised controlled trial. Setting 32 general practices in London and south Essex. Participants 720 women considering breast feeding. Main outcome measures Primary outcome was prevalence of any breast feeding at six weeks. Secondary outcomes were the proportion of women giving any breast feeds, or bottle feeds at four months, duration of any breast feeding, time to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
152
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(157 citation statements)
references
References 11 publications
1
152
2
2
Order By: Relevance
“…Moreover, teaching the fathers seems to represent a valid and cost-effective intervention 21,23,24 when we consider that other educational interventions led by volunteer counselors and health professionals have shown a not yet well-established influence on breastfeeding rates. [6][7][8][9] The advantages of intervention based on the fathers rather than on volunteers and health professionals can be represented by the emotional support and the continuity of care that the father can provide and by the fact that some women can be reluctant to ask for help from people who are not part of the family. 6 The weaknesses of this study are represented by the limited numbers of participants enrolled, by the single-hospital setting, and by sequential rather than random allocation of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, teaching the fathers seems to represent a valid and cost-effective intervention 21,23,24 when we consider that other educational interventions led by volunteer counselors and health professionals have shown a not yet well-established influence on breastfeeding rates. [6][7][8][9] The advantages of intervention based on the fathers rather than on volunteers and health professionals can be represented by the emotional support and the continuity of care that the father can provide and by the fact that some women can be reluctant to ask for help from people who are not part of the family. 6 The weaknesses of this study are represented by the limited numbers of participants enrolled, by the single-hospital setting, and by sequential rather than random allocation of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] The advantages of intervention based on the fathers rather than on volunteers and health professionals can be represented by the emotional support and the continuity of care that the father can provide and by the fact that some women can be reluctant to ask for help from people who are not part of the family. 6 The weaknesses of this study are represented by the limited numbers of participants enrolled, by the single-hospital setting, and by sequential rather than random allocation of the participants. However, we think that because the participants and the interviewers were genuinely blind to the study design, the method that we chose provided valid data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the studies of lay support that reported exclusive breastfeeding, there was a marked reduction in the cessation of exclusive breastfeeding before the last study assessment (RR 0.72, 95% CI 0.57 to 0.90). 114,355,356,[358][359][360] There was heterogeneity among these studies (I 2 = 96.3%). Further subgroup analysis indicated that this effect was significant within the first 3 months (RR before 4-6 six weeks 0.66, 95% 0.46 to 0.96; RR before 2 months 0.44, 95% CI 0.26 to 0.73; RR before 3 months 0.42, 95% CI 0.31 to 0.57)…”
Section: Discussionmentioning
confidence: 99%
“…Trials that used laypeople to deliver the intervention demonstrated a significant reduction in breastfeeding cessation at the time of the last study assessment (RR 0.86, 95% CI 0.76 to 0.98). 88,114,[354][355][356][357][358][359][360] Significant heterogeneity was present among these studies (I 2 = 75.6%). Further subgroup analysis did not reveal a statistically significant effect at any time point up to 4 months.…”
Section: Discussionmentioning
confidence: 99%